Family of step‐up DC/DC converters with fast dynamic response for low power applications. Issue 14 (1st November 2016) - Soltani, Mohsen; Mostaan, Ali; Siwakoti, Yam Prasad; Davari, Pooya; Blaabjerg, Frede
Abstract : This study presents a family of novel step‐up DC/DC converters which do not have a right half plane zero in their transfer function resulting in faster dynamic behaviour of the converters under the load variation. In addition, the voltage stress on all the active switches and diodes is as low as the input voltage level. The basic topology of this converter has a voltage gain of up to two in steady state. The derivatives of the converter are realised by adding a switched capacitor voltage multiplier cell in order to increase the voltage gain further. The most salient feature of these converters is presence of only two switches in the basic converter and its derivatives. The dynamic performance of the proposed converter and its first derivative is analysed by small‐signal model using the state‐space averaging method. The theoretical model is verified by experiments using GaN high‐electron‐mobility transistors with 1 MHz switching frequency.